2020
DOI: 10.3390/jof7010015
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Solanum melongena and Vitis vinifera Plants by Botrytis cinerea Is Strongly Reduced by the Exogenous Application of Tomato Systemin

Abstract: Plant defense peptides are able to control immune barriers and represent a potential novel resource for crop protection. One of the best-characterized plant peptides is tomato Systemin (Sys) an octadecapeptide synthesized as part of a larger precursor protein. Upon pest attack, Sys interacts with a leucine-rich repeat receptor kinase, systemin receptor SYR, activating a complex intracellular signaling pathway that leads to the wound response. Here, we demonstrated, for the first time, that the direct delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…One of these is Sys, which acts as a DAMP in tomato plants following insect or mechanical damage by triggering plant immunity (Ryan, 2000; Ryan and Pearce, 2003). Coppola et al (Coppola et al, 2019c) and Molisso et al (Molisso et al, 2021) demonstrated that the exogenous supply of the peptide to intact healthy plants severely counteracted S. littoralis and B. cinerea fungal growth. These results are likely linked to the induction of plants defense-related genes through the accumulation of active compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these is Sys, which acts as a DAMP in tomato plants following insect or mechanical damage by triggering plant immunity (Ryan, 2000; Ryan and Pearce, 2003). Coppola et al (Coppola et al, 2019c) and Molisso et al (Molisso et al, 2021) demonstrated that the exogenous supply of the peptide to intact healthy plants severely counteracted S. littoralis and B. cinerea fungal growth. These results are likely linked to the induction of plants defense-related genes through the accumulation of active compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that exogenous Sys supply induces an array of defense-related responses leading to the final accumulation of proteinase inhibitors (PINs) and other molecules able to interfere with the colonization of fungal pathogens or the growth and survival of herbivores (Coppola et al, 2019c; Molisso et al, 2021). Also, Sys-treated plants proved to be more attractive for pest natural enemies as a consequence of the modified blend of volatile compounds emitted, which is known to be used by predators and parasitoids of phytophagous insects to locate their preys and hosts (Ninkovic et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifungal assay was carried out as already reported ( Pastor-Fernández et al, 2020 ; Molisso et al, 2021 ). A sterile 12-well plate was filled with potato dextrose broth (PDB 1/2) medium, containing ProSys fragments at the final concentration of 100 fM.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, transgenic plants expressing prosystemin reduce lesions by at least 50% from Phytophthora infestans, a pathogen that causes late blight [ 104 ]. Systemin peptides have been successfully isolated from tomato, sprayed onto grapevine ( Solanum melongena ) and eggplant ( Vitis vinifera ) plants infected with B. cinerea [ 105 ] at a concentration of 100 pM, and efficiently delayed necrosis of the infected plants.…”
Section: Antimicrobial Proteinsmentioning
confidence: 99%